An Integrative Pan-Cancer Analysis Revealing LCN2 as an Oncogenic Immune Protein in Tumor Microenvironment - Xu, Wen-Xiu; Zhang, Jian; Hua, Yu-Ting; Yang, Su-Jin; Wang, Dan-Dan; Tang, Jin-Hai (Frontiers in Oncology, 2020)
Background: Lipocalin 2 (LCN2), an innate immune protein, plays a pivotal role in promoting sterile inflammation by regulating immune responses. However, the role of LCN2 in cancers remains unclear. This study aimed to explore the correlation between LCN2 expression and immunity and visualize its prognostic landscape in pan-cancer. Methods: Raw data related to LCN2 expression in cancer patients were obtained through TCGA and GTEx databases. Besides, we investigated the genomic alterations, expression pattern and survival analysis of LCN2 in pan-cancer across multiple databases, including cBioPortal and GEPIA database. The correlations between LCN2 and tumor immune infiltration was investigated via TIMER, and we applied CIBERSORT and ESTIMATE computational methods to calculate the proportion of tumor-infiltrating immune cells (TIIC) and the amount of immune and stromal components from TCGA database. Protein-Protein Interaction analysis was performed in GeneMANIA database, and gene functional enrichment was performed by Gene Set Enrichment Analysis (GSEA). Results: In general, compared with that in normal tissue, tumor tissue had a higher expression level of LCN2. Elevated expression of LCN2 was related to poor clinical regimen with OS and RFS. There were signiﬁcant positive correlations between LCN2 expression and immune inﬁltrates, including B cells, CD8+ T cells, CD4+ T cells, neutrophils, macrophages, and dendritic cells. Furthermore, markers of inﬁltrating immune cells, exhibited different LCN2-related immune inﬁltration patterns. GSEA showed that the expression of LCN2 is related to retinol metabolism, metabolism of xenobiotics by cytochrome P450 and drug metabolism cytochrome P450. Conclusions: These findings suggested that LCN2 might serve as a biomarker for immune infiltration and poor prognosis in cancers, which offered an extra insight for therapeutics of cancers.